2018
DOI: 10.5755/j01.sace.22.1.20006
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Copper Slag Waste and Heavy-weight Aggregates for Production of Pre-cast shielding Concrete Elements

Abstract: Concrete as a versatile building material can provide physical and biological shielding against ionizing radiation. In addition to nuclear reactor covers, facilities requiring radiation protection are radiological and X-ray laboratories in hospitals or health centres. The function of radiation protection can be met by heavyweight concrete, whose shielding properties are largely derived from the high-density aggregates. One of the possible construction methods of shielding walls in healthcare buildings is the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…45 An economic analysis of the costs of producing concrete with a density higher than 3200kg/m 3 with or without copper slag waste showed that the copper slag concrete, regardless of the type of heavy-weight aggregate used, is clearly more economical than the concrete containing similar coarse aggregates and sand as a fine aggregate. 46…”
Section: Copper Slag As a Replacement Of Fine Aggregatementioning
confidence: 99%
See 1 more Smart Citation
“…45 An economic analysis of the costs of producing concrete with a density higher than 3200kg/m 3 with or without copper slag waste showed that the copper slag concrete, regardless of the type of heavy-weight aggregate used, is clearly more economical than the concrete containing similar coarse aggregates and sand as a fine aggregate. 46…”
Section: Copper Slag As a Replacement Of Fine Aggregatementioning
confidence: 99%
“…54 The presence and absence of SF both showed a continual increase in the resistance to chloride penetration from the conventional concretes to the high strength concretes. 46 The copper slag admixed concrete is considered under the grouping of "very low" as per ASTM C1202 chloride penetration values indicating its low permeability. 56 The rapid chloride penetrability (AASHTO T277 and ASTM C 1202) of concretes studied show that mineral admixtures admixed concrete due to its denser pore structure confirmed best resistivity towards chloride ingression as compared to normal concrete.…”
Section: Mechanical Properties Compressive Strengthmentioning
confidence: 99%
“…However, it can be utilised again, and its potential applications are described, amongst others, in [10,11]. Due to its composition and physical form, copper slag can be used in the production of concrete as a partial or total substitute for sand [12][13][14][15] even in lightweight concrete [16]. In contrast to e.g., fine fractions of recycled concrete aggregate, the material is also suitable for the production of high-quality concrete, without compromising its quality, and some properties even improve in comparison with concrete manufactured with sand [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Copper slag as fine aggregate is widely used. Its use was tested both in lightweight concrete and in prefabricated heavy concrete elements (Kubissa, Jaskulski, Ng, & Chen, 2018). Its pozzolanic properties and synergic increase in mechanical properties of material when used together with fly ash make it a valuable material for the preparation of CLSM mixtures with very low cement content (Jaskulski & Kubissa, 2019).…”
Section: Introductionmentioning
confidence: 99%